Deberes jurídicos y convicciones morales en el ordenamiento español - Ciáurriz, María José (Revista de Derecho Político, 2012)
Human rights literature has long been dealing with the issue of conscientious objection, which has recently been described, very adequately, as «a conflict between conscience and law». Based on this premise, this article brings this topic to a higher, more general level and refers to the moral convictions —of ethical or religious nature— that any individual may hold, and to the conduct that may follow such convictions in view of the legal duties imposed by the law on citizens. This is no doubt a universal problem: the consistence of human behavior as the product of personal ethics, and the related issue of how States are to respond when personal conscience and the existing legal order are incompatible. The author, as suggested in the title, deals with these matters in the context of Spanish Law, approaching conscientious objection as a multi-faceted issue. Special attention is paid to the actual/possible/ideal solution of a number of factual situations with a view to arriving at an outcome where no one is constrained to disregard his legal duties to the detriment of his freedom and personal rights. This work contemplates conscientious objection from a very up-to-date perspective, studying the relevant legal rules on the issue, which is presented as an ethical-legal conflict. In this type of situation, it is not legitimate to disregard the needs of any of the conflicting parties, as in a human rights framework all of them should be involved in fulfilling the twofold duty of abiding by the law and respecting one’s own conscience.